The Holy Spirit : works & gifts - Bloesch, Donald G., 1928-2010. (Downers Grove, IL : InterVarsity Press, 2000)
"In this encyclopedic volume Donald Bloesch brings breadth of learning and careful analysis to the works and gifts of the Holy Spirit. From within a biblical framework, he explores issues such as baptism, conversion, assurance, spiritual gifts, sanctification, Christian experience and the gender of the Holy Spirit. His survey of approaches to the Holy Spirit taken throughout church history, in recent religious movements, and within Pentecostal, Reformed, Roman Catholic and Eastern Orthodox traditions is marked with charity and insight."--BOOK JACKET.
1. Introduction -- 2. The Contemporary Debate -- 3. The Descent of the Spirit in Biblical Understanding -- 4. Fathers, Enthusiasts & Mystics -- 5. Reformation Perspectives -- 6. Post-Reformation Renewal Movements -- 7. New Challenges to Traditional Faith -- 8. Pentecostalism -- 9. Recent Developments in Theological Thought -- 10. The Holy Spirit: Person & Mission -- 11. The Highway of Holiness.
Includes bibliographical references (p. [343]-396) and indexes.
Keywords: Holy Spirit